The Impact of Information Technology Implementation in Accounting on the Effectiveness of Management Decision Making: A Qualitative Study - Putro, Harjono Padmono (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to investigate the impact of information technology (IT) implementation in accounting on the effectiveness of management decision-making, focusing on the role of advanced IT tools such as ERP systems, cloud computing, and blockchain in enhancing decision quality, especially in small and medium-sized enterprises (SMEs). A qualitative research design was employed, utilizing a systematic literature review approach to gather and analyze relevant studies on IT implementation in accounting. The research examined various factors affecting decision-making processes and the benefits and challenges of integrating IT into accounting systems. The findings indicate that implementing IT significantly enhances the quality of managerial decision-making by providing real-time, accurate data. This study demonstrates how advanced accounting systems' high-quality information directly affects the effectiveness and efficiency of decision-making. Moreover, external factors such as regulatory changes and market dynamics are critical in moderating the relationship between IT and decision-making outcomes. The study highlights the need for organizations, particularly SMEs, to prioritize IT integration in their accounting practices. Practical implications include fostering a culture of innovation, providing comprehensive training, and regularly assessing IT infrastructure to improve decision-making processes and maintain a competitive edge.